Molecular profiling of advanced non-small cell lung cancer in the era of immunotherapy approach: a multicenter Italian observational prospective study of biomarker screening in daily clinical practice. Issue 4 (28th January 2021) - Vavala, Tiziana; Malapelle, Umberto; Veggiani, Claudia; Ludovini, Vienna; Papotti, Mauro; Leone, Alvaro; Graziano, Paolo; Minari, Roberta; Bono, Francesca; Sapino, Anna; Manotti, Laura; Troncone, Giancarlo; et al.
Abstract : Aims: Heterogeneous implementation of molecular tests in current diagnostic algorithm at a European and international level is emerging as a major issue for efficient lung cancer molecular profiling. Methods: From May 2017 until October 2017, N=1612 patients referring to 13 Italian institutions were selected, at advanced stage non-small cell lung cancer (NSCLC), and prospectively evaluated. Principal endpoints were: the percentage of diagnoses performed on cytological and histological material, the proportion of requests for epidermal growth factor receptor (EGFR) mutational status, and resistance mutations detected on tissue and/or liquid biopsy samples after first-generation or second-generation tyrosine kinase inhibitors, the proportion of requests for anaplastic lymphoma kinase (ALK) gene rearrangements, ROS proto-oncogene 1 (ROS1) and Kirsten Rat Sarcoma (KRAS) determinations, the proportion of requests for programmed death-ligand1 (PD-L1) evaluation and, finally, the different assays used for the detection of EGFR mutations, ALK and ROS1 gene rearrangements and PD-L1 expression. Results: Of 1325 patients finally included, only 50.8% requests were related to driver mutations with target agents already available in first-line at that preplanned time, while 49.2% were associated with PD-L1, ROS1, KRAS and others. Multiplex genomic assays (such as next-generation sequencing) were considered by all participating centres. Conclusions: To the best of our knowledge, this is the first study in a 'real-life daily practice' involving both pathologists and oncologists evaluating routinely workflow and trends towards improvements in molecular requests. Collected data aim to describe the applied algorithms and evolution of molecular screening for stage IV NSCLC in clinical practice.